Influence of Career Development, Organizational Culture, and Adaptive Leadership on Work Motivation of Employees - Nely Marlina; Sumiati (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the influence of career development, organizational culture, and adaptive leadership on the work motivation of employees at the Sungai Penuh City Health Office. This study used a quantitative approach with a survey method, where data were collected through questionnaires distributed to 50 employees as respondents. Data analysis techniques used included validity testing, reliability testing, descriptive analysis, classical assumption testing, and multiple linear regression analysis using the SPSS program. The results showed that partially, career development, organizational culture, and adaptive leadership had a positive and significant effect on employee work motivation. Organizational culture was the variable with the most dominant influence on work motivation. Simultaneously, these three independent variables significantly influenced employee work motivation. The coefficient of determination of 0.583 indicates that career development, organizational culture, and adaptive leadership explained 58.3% of the variation in employee work motivation, while the remainder was influenced by factors outside the research model. Based on these results, it is concluded that improving employee work motivation at the Sungai Penuh City Health Office requires an integrated approach through strengthening career development policies, establishing a positive organizational culture, and implementing adaptive leadership that is responsive to changes and employee needs.